2022
DOI: 10.1107/s2052252522006996
|View full text |Cite
|
Sign up to set email alerts
|

A general method for directly phasing diffraction data from high-solvent-content protein crystals

Abstract: A procedure is described for direct phase determination in protein crystallography, applicable to crystals with high solvent content. The procedure requires only the diffraction data and an estimate of the solvent content as input. Direct phase determination is treated as a constraint satisfaction problem, in which an image is sought that is consistent with both the diffraction data and generic constraints on the density distribution in the crystal. The problem is solved using an iterative projection algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Direct methods play a crucial role in solving protein crystal structures directly from diffraction data without relying on any prior information, such as heavy-atom derivatives or homology structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Traditional direct methods for phasing small-molecule crystals [17][18][19][20][21][22][23][24][25][26][27][28][29] use the triplet relation and the tangent formula [21][22][23], the vive la différence algorithm (VLD) [28], the electron-density modification (EDM) and the difference electrondensity modification (DEDM) [29], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct methods play a crucial role in solving protein crystal structures directly from diffraction data without relying on any prior information, such as heavy-atom derivatives or homology structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Traditional direct methods for phasing small-molecule crystals [17][18][19][20][21][22][23][24][25][26][27][28][29] use the triplet relation and the tangent formula [21][22][23], the vive la différence algorithm (VLD) [28], the electron-density modification (EDM) and the difference electrondensity modification (DEDM) [29], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is cyclic and easy to implement with a large convergence radius when the crystal has a high solvent content. While the direct method for macromolecule crystals has been successfully tested in retrieving known crystal structures of proteins and viruses [8][9][10][11][12][13][14][15][16], it has not been applied to solve the atomic structure of unknown protein crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, significant effort has been devoted to the development of various algorithms for de novo protein structure determination (Uso ´n & Sheldrick, 1999;Dorset, 2000;Miller et al, 2001;Rodrı ´guez et al, 2009;Liu et al, 2012; ISSN 2059-7983 He & Su, 2015;Kingston & Millane, 2022). Direct phase determination using iterative projection algorithms (IPAs; Millane & Lo, 2013;Lo et al, 2015) has shown potential as an effective tool for ab initio phase determination in protein crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…Fienup (1982) also extended the G-S algorithm to work better in settings similar to X-ray crystallography. Similar methods to that developed by Fienup have occasionally been applied to solve the crystallographic phase problem, but only in special cases where the crystals have very high solvent content (He & Su, 2015;He et al, 2016a;Kingston & Millane, 2022).…”
Section: Introductionmentioning
confidence: 99%